Freezing Improves Instrumental Tenderness of Strip Steaks Purchased at Retail Grocery Stores - A. M. Collins; J. A. Unruh; T. A. Houser; S. Stroda (Kansas Agricultural Experiment Station Research Reports, 2016)
When meat is frozen cell membranes can be damaged, which may lead to lower water holding capacity and higher cooking losses. Several researchers have indicated that freezingLongissimusmuscle (strip loin) steaks may lower Warner-Bratzler shear force, a measurement to objectively measure beef tenderness, compared with steaks not previously frozen. The objective of this study was to determine the effect of freezing on beef tenderness and cooking characteristics of strip steaks purchased from grocery store outlets.
Keywords: tenderness; retail; longissimus